2015
DOI: 10.1016/j.ygeno.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of human Chlamydia pneumoniae isolates from respiratory, brain and cardiac tissues

Abstract: Chlamydia pneumoniae is an obligate intracellular bacterium implicated in a wide range of human diseases including atherosclerosis and Alzheimer's disease. Efforts to understand the relationships between C. pneumoniae detected in these diseases have been hindered by the availability of sequence data for non-respiratory strains. In this study, we sequenced the whole genomes for C. pneumoniae isolates from atherosclerosis and Alzheimer's disease, and compared these to previously published C. pneumoniae genomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 83 publications
1
26
0
Order By: Relevance
“…Interestingly, lipopolysaccharide (LPS) from periodontal pathogens such as P. gingivalis and T. denticola was isolated from short-term postmortem Alzheimer's disease human brains, suggesting that virulence factors from these pathogens could play a role in development of brain inflammation and Alzheimer's disease [71] . Moreover, bacteria such as the periodontal pathogen T. denticola [72] and C. pneumoniae [73] , [74] were detected in postmortem Alzheimer's disease brains, suggesting that besides inflammatory mediators, some periodontal pathogens may invade the brain by crossing the brain-blood barrier. This was confirmed in animal studies, which showed the presence of P. gingivalis in mouse brains [75] .…”
Section: Relationship Between Oral and Non-oral Systemic Diseasementioning
confidence: 99%
“…Interestingly, lipopolysaccharide (LPS) from periodontal pathogens such as P. gingivalis and T. denticola was isolated from short-term postmortem Alzheimer's disease human brains, suggesting that virulence factors from these pathogens could play a role in development of brain inflammation and Alzheimer's disease [71] . Moreover, bacteria such as the periodontal pathogen T. denticola [72] and C. pneumoniae [73] , [74] were detected in postmortem Alzheimer's disease brains, suggesting that besides inflammatory mediators, some periodontal pathogens may invade the brain by crossing the brain-blood barrier. This was confirmed in animal studies, which showed the presence of P. gingivalis in mouse brains [75] .…”
Section: Relationship Between Oral and Non-oral Systemic Diseasementioning
confidence: 99%
“…Additionally, the higher incidence of both Chlamydophila pneumoniae and Hp DNA, by PCR, in atherosclerotic plaques of carotic artery signifies that these microorganisms may play a role in the pathogenesis of atherosclerosis and concomitant AD; subclinical carotid atherosclerosis is associated with worse cognition among those at higher risk of AD and coronary artery disease (CAD) increases the subsequent risk of AD; and both Chlamydophila pneumoniae and Hp are associated with development of CAD . In this respect, the mentioned Chlamydophila pneumoniae is observed in the brain, lungs, and cardiovascular system . Moreover, Chlamydophila pneumoniae is an obligate intracellular respiratory pathogen that could access the brain following infection and trafficking of monocytes through the BBB.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Until recently, the majority of fully sequenced C. pneumoniae whole genomes were from strains that were isolated from respiratory pathologies [ 10 , 19 , 20 ], and demonstrated highly conserved nucleotide sequence content and gene order. Recently, several genomes from respiratory and cardiovascular strains were reported, as were whole genome sequences from atherosclerotic and Alzheimer’s C. pneumoniae strains, which allowed for comparison of strains isolated from different diseases, and demonstrated that only minor genetic differences were found between these strains [ 9 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%